The Relationship Between Students' Perceptions of Spiritual and Religiosity Extracuriculars With The Independent Character of MTs Students in Bekasi Timur District, Bekasi City - Fachrunnisa, Munis; Hidayat, Yayat; Darwis (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The independent character of students is an important thing that must be possessed in the teaching and learning process. This study aims to determine whether there is a relationship between students' perceptions of Spiritual and Religiosity extracurriculars partially and together with the independent character of students at the MTS Level in East Bekasi District, Bekasi City. The research method used is a quantitative method with a correlation research type. Data analysis used the partial Paired T-Test, Anova Test, and the determinant coefficient test used the SPSS application. This study used random sampling with a sample of 187 students from a population of 352 students. The subjects in this study were high school level students specifically for class XI. The results of this study indicate that all research hypotheses are proven (sig.5%). Variable (X1) students' perceptions of Spiritual extracurriculars and variable (X2) Religiosity have a significant relationship with variable (Y) students' independent character. In addition, there is also a partial relationship between X1 and Y and X2 and Y.